Understanding visitor flow and behaviour in developing tourism-service-oriented villages by space syntax methodologies: a case study of Tabian Rural Section of Qingshan Village, Hangzhou - Shuqin Wang; Yan Huang; Tianjie Li (Journal of Asian Architecture and Building Engineering)
In the built environment (BE) of tourism-service-oriented villages, understanding visitor flow volumes and behaviours is crucial for guiding space revitalization and tourism management. This research uncovers quantitative relationships between visitor flow volume, spatial visual exposure, and visitors’ behaviour at 12 sites in the Tabian Rural Section of Qingshan Village, a typical tourism service-oriented village in Hangzhou. The methodologies employed in this study are based on two space syntax algorithms: 3-D isovist analysis and agent-based models (ABMs). Visual Exposure Rates (VERs) in 3-D isovists along visitors’ routes were calculated using parametric programming, and visitor flow simulation was conducted using two ABMs. Real-world visitor volumes (RWFVs) and visitors’ behaviors were also recorded during an in-situ survey. A comprehensive correlation analysis revealed multiple associations. The results demonstrated that combined simulations from ABM I, and VERs explained 50.5% of the overall variability in RWFVs. Notably, VERs were found to be associated with visitors’ behaviours of photography and seating, while the outputs from ABM I showed a moderate correlation with RWFVs. This study innovatively combines space syntax models for extended application in the research of rural BEs, providing guidance for optimizing strategies to improve spatial configuration in homogeneous villages.